An Algorithm to Determine Non-Perfect Colorings that arise from Plane Crystallographic Groups - De Las Peñas, Ma. Louise Antonette N (Archīum Ateneo, 1999)
This paper presents a computer algorithm that assists us in our research on non-perfect colorings of plane crystallographic patterns.